2015
DOI: 10.1128/aem.03518-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Norspermidine and Spermidine on Biofilm Formation by Potentially Pathogenic Escherichia coli and Salmonella enterica Wild-Type Strains

Abstract: Polyamines are present in all living cells. In bacteria, polyamines are involved in a variety of functions, including biofilm formation, thus indicating that polyamines may have potential in the control of unwanted biofilm. In the present study, the effects of the polyamines norspermidine and spermidine on biofilms of 10 potentially pathogenic wild-type strains of Escherichia coli serotype O103:H2, Salmonella enterica subsp. enterica serovar Typhimurium, and S. enterica serovar Agona were investigated. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…Our observations of a limited effect of norspermidine on bacterial cell growth for most species contrast with previous findings reported by Hobley et al, who noted significantly impaired growth of B. subtilis at concentrations ≥ 1 mM (Hobley et al 2014). Our findings showing minimal effect of norspermidine on planktonic growth of the Gram negative species evaluated herein are consistent previous studies evaluating the effect of norspermidine at concentrations up to 5 mM on the planktonic growth of E. coli and Salmonella enterica (Nesse et al 2015). Similarly, studies evaluating the activity of the related polyamine, spermine, on biofilms of Neisseria gonorrhoeae have reported that concentrations as high as 4 mM inhibited biofilm formation but had no notable effect on bacterial growth (Goytia et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our observations of a limited effect of norspermidine on bacterial cell growth for most species contrast with previous findings reported by Hobley et al, who noted significantly impaired growth of B. subtilis at concentrations ≥ 1 mM (Hobley et al 2014). Our findings showing minimal effect of norspermidine on planktonic growth of the Gram negative species evaluated herein are consistent previous studies evaluating the effect of norspermidine at concentrations up to 5 mM on the planktonic growth of E. coli and Salmonella enterica (Nesse et al 2015). Similarly, studies evaluating the activity of the related polyamine, spermine, on biofilms of Neisseria gonorrhoeae have reported that concentrations as high as 4 mM inhibited biofilm formation but had no notable effect on bacterial growth (Goytia et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The activity of norspermidine was observed to be both species- and strain-dependent, with A. baumannii isolates being the most sensitive to these effects. Strain- and species-dependent differences in the response of isolates to norspermidine are consistent with previous studies and have been previously documented (Nesse et al 2015; Ramon-Perez et al 2014). This may be due differences between strains in their ability to develop biofilms on abiotic surfaces, differences in the composition of polymeric matrix, and undefined mechanisms impeding biofilm formation or dispersal initiation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations